The Yeast PHO Promoters as Paradigm for Transcriptional Regulation by Chromatin Remodelling: Current State of the Art - Slobodan Barbarić (Food Technology and Biotechnology, 2014)
It has been widely acknowledged that modulation of chromatin structure at the promoter region influences the usage of factor binding sites and thus provides first, important level of transcriptional regulation. Chromatin-remodelling complexes utilize the energy of ATP hydrolysis to disassemble nucleosomes, and their functions are prominently correlated with promoter activation and also repression. Mechanistic details of individual steps and their orchestration in complex remodelling events, as well as regulatory mechanisms controlling remodeller activity, are subjects of current and future studies. The yeast PHO5 promoter was the first and still is one of the best characterized examples of a massive chromatin transition associated with transcriptional activation. Studies with this promoter provided several breakthrough findings and established basic principles of chromatin-remodelling process. Recent studies have revealed a network of five remodellers from all four remodeller subfamilies involved in this chromatin transition. Importantly, requirement for chromatin remodellers at the PHO8 as well as at PHO84 promoter, activated by the same transactivator as PHO5, are rather different. All these findings point out that chromatin remodelling process is in general even more complex than presumed, and it could be expected that further studies with the well-established PHO promoter system will be rather valuable for its further understanding.